UNDERSTANDING THE DIGITAL HEALTH KNOWLEDGE ECOSYSTEM: ANALYZING THE MARKETING AND COMMUNICATION PRACTICES OF PATIENT INFLUENCERS, PHARMACEUTICAL AND TELEHEALTH COMPANIES - Leskovac, Milana (AoIR Selected Papers of Internet Research, 2026)
Social media-fuelled popularity of the so-called ‘miracle drugs’ Ozempic and Wegovy prompted many concerns about off-label prescriptions, use without proper consultation, new compounding pharmacy formulations, the adverse side-effects of overuse, etc. While these issues are not new, emerging novel entanglements of many actors with conflicting interests—including patient influencers, telehealth and pharmaceutical companies—are involved in the assembly of health knowledge through product promotion and social media communication that raise crucial issues of how trust is multiply mediated and health/medical knowledge constructed and distributed. For instance, influencers create and maintain ‘authentic’ personas, gaining follower trust and pharmaceutical companies, long struggling with brand reputation, leverage these personas mediating public trust and increasing the ‘invisible hands’ (Sismondo 2018) with which they shape health/medical knowledge. However, the extent of commercial influence remains unclear, which is crucial for understanding the formation and relationships within the ecosystem of health knowledge online. Using an STS and digital mediatization lens, this paper draws upon key concepts such as expertise, trust, epistemic democratization and competition, ‘civic epistemologies’, and entanglements (Hepp and Couldry 2023; Jasanoff 2022; Marres 2018) to understand health communication relations of these actors online. Presenting findings from the first phase of my doctoral research—a hermeneutic content analysis of patient influencer Instagram and TikTok videos—this presentation focuses on understanding what is communicated, by whom, and how, revealing shifting marketing and communication practices on social media that ultimately work to restructure this knowledge ecosystem and impact public health choices.